(untitled) (Journal of Contemporary Philology, 2018)
Review of the Dictionary of Croatian Animal Idioms, Ivana Vidović Bolt, Branka Barčot, Željka Fink Arsovski, Barbara Kovačević, Neda Pintarić,Ana Vasung, Zagreb, 2017